Peranan Badan Pengelola Lingkungan Hidup dalam Pengembangan Potensi Sumber Daya Alam - Ali Hasan Zein; Syamsuddin RS; Rohmanur Aziz (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this study is to analyze the implementation of EIA in the Environmental Management Agency in the development of natural resource potential. Analyzed from the norms, concepts, and behavior of human resources contained in BPLHD West Java Province. The role theory proposed by Levinson was used to analyze the problems in this study. In his statement, that role covers three things including norms that become rules to guide someone in society, concepts that individuals will do in society as an organization, as well as individual behavior that is important for the social structure of society. This research is a qualitative research using descriptive method. Data was collected through observation, interviews, and documentation studies. Analysis of data in this study uses interpretations or interpretations of logic that are related to the context of Islamic Community Development. The results showed that the Regional Environmental Management Agency of West Java Province in the development of natural resource potential through Analysis of Environmental Impacts had standard rules issued by the Ministry of Environment, namely the Minister of Environment Regulation No. 08/2013, which regulates the rules and governance, the concept formulated, and the performance of its human resources. The Environmental Management Agency in developing natural resource potential through an analysis of environmental impacts, has an effect.